PERBANDINGAN UKURAN GIGI DAN DIMENSI LENGKUNG ANTARA GIGI TANPA BERJEJAL DENGAN GIGI BERJEJAL - Steven Wijaya (Universitas Prima Indonesia, 2021)
Tooth size and arch dimensions are hereditary factors that play a role in the occurrence of crowding teeth. The purpose of this study was to determine the difference in tooth size and arch dimensions between crowding and crowding teeth. This type of research is an observational study with a cross sectional approach. The sample of this study consisted of two groups. The sample of this study was a dental study model, which consisted of 36 pairs in each group. The results showed the total mesio-distal width of the maxillary anterior teeth (45.95 mm and 48.26 mm), the mandibular anterior teeth (35.92 mm), and 38.16), the maxillary teeth (95.82 mm and 99.47 mm), the mandibular teeth (87.60 mm and 91.50 mm), the inter-canine width maxillary buccal region (37.03 mm and 34.85 mm), maxillary inter-canine width palatal region (26.53 mm and 25.69 mm), buccal area of ​​mandibular inter-canine width (28.38 mm and 27.75 mm), the mandibular inter-canine width in the lingual area (20.38 mm and 19.90 mm), the maxillary inter-molar width in the buccal area (62.73 mm and 60.60 mm), the maxillary inter-molar width in the palatal area (37.86 mm and 35.10 mm), mandibular inter-molar width buccal area (56.51 mm and 55.31 mm), mandibular inter-molar width lingual area (34.10 mm and 31.66 mm), arch length maxillary arch (37.57 mm and 37.76 mm), mandibular arch length (32.63 mm and 32.77 mm), maxillary arch perimeter (96.95 mm and 94.68 mm), and mandibular arch perimeter (87.86 mm and 85.83 mm), Bolton's anterior ratio (78.19% and 79.13%), and Bolton's overall ratio (91.43% and 92.03%). The conclusion of the study showed that the crowding group had larger tooth size, narrower arch width, narrower arch perimeter, longer arch length, and larger anterior ratio and Bolton overall ratio compared to the crowding group.